Social Rights and Migrant Realities: Migration Policy Reform and Migrants’ Access to Health Care in Costa Rica, Argentina, and Chile - Noy, Shiri (2016)
Immigration poses a significant challenge to states’ existing social protection systems, especially in developing countries that are already struggling to provide social services for their citizens. In particular, immigration produces a tension between citizenship rights—those extended only to citizens, and social rights—rights extended by the state to others within their national territory. Immigration raises questions not only about the rights and access of migrants to health and other social services but also the level and quality of provisions to citizens. We draw on literatures on welfare regimes in Latin America, welfare magnets, and the legitimacy of social rights to examine the nexus of migration and health care policy in Costa Rica, Argentina, and Chile—three countries that have recently pursued immigration reform. We argue that variation in the extension of immigrants’ social rights to health is explained by the interaction of existing migration and social policies, the nature of the health care system in each country, and, in some cases, international and regional norms.